Could Agnihotra yagya have any role in the prevention and management of epidemics as COVID-19: A scientific perspective - Sachitra Singh; Shagufta Rahat; Vijay Kumar Rai; Shalini Rai (Wolters Kluwer Medknow Publications, 2022)
Objective: COVID-19 has challenged the healthcare systems of the world and was declared as public health emergency of international concern. With more than 55 million cases of COVID-19 and 1,355,769 deaths globally, the world is still searching for cure. In the absence of any definite treatment, the practices of prevention have occupied the central role, with governments across the globe promoting the same. In the context of this global catastrophe, an ancient Indian practice of Agnihotra yagya (fire ablations) is being presented here with the scientific evidences to explore the possibility before the world for its repurposing for prevention and management of epidemics as COVID-19. Data Source: Databases of Google Scholar and PubMed were searched with the keywords anti-microbial effects and their different combinations and permutations along with hand search, benefits, of Agnihotra, research, Yagya. Review Methods: Relevant articles were downloaded and stored in a folder. Then, they were screened for their relevance after reading, and finally, 70 articles were included in the study, bringing the scientific aspects in a systematic manner to put forward the scientific aspects. Results and Conclusion: The existing evidence support the anti-microbial, healing, energizing effects along with beneficial effects on the comorbidities of patients, thus decreasing the percentage and intensity of morbidity and mortality rates of diseases. With the above observations, Agnihotra Yagya may be researched more extensively, bringing out more evidences for the real utilization of this practice in the fight against COVID 19.